A study on the effectiveness of computerised system in NBCT / Shalinda Baharoom Shah - Baharoom Shah, Shalinda (1996)
This thesis has been written to study on the effectiveness of computerized system in North Butterworth Container Terminal at Penang Port Sdn. Bhd since this is the first port in Malaysia that are using fully computerized system in its terminal. This study is not only for the academic purpose but also for the company reference. The opportunity has been taken to study on the effectiveness of the system itself (PELKON II). This study has done the analysis on the port performance of the North Butterworth Container Terminal and Butterworth Container Terminal. The purpose of studying these two terminals is to know which terminal give a better performance. Therefore, the comparison between these two terminals has been done. Finally recommendation has been made to improve the port performance.